The Link between Speech Mastery and Writing Achievement: The Case of Madrasah Students in South Sumatera - SHOHIBUL KAHFI (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2019)
This study investigated the link between students’ parts of speech mastery and their achievement in writing skill. This study was aimed at finding out whether or not there was any significant link and significant influence among the two variables. The population of the study was tenth grade Madrasah students in South Sumatera. There were 330 students from five classes as the population in this study. However, 96 students were taken as the sample of this study. There were two variables involved in this study, students’ parts of speech mastery (variable X), and writing achievement (variable Y). The score of parts of speech mastery was taken from multiple choice questions, while the student’ writing achievement was taken from the test which was scored based on experts’ judgment. Based on the data analysis, it was found that the r-obtained (.293) was higher than r-table (.200). Then, the level of probability (p) significance (sig.2-tailed) was .443. It means that p (.004) was lower than .05. Thus, null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. Based on the findings, it was concluded that there was significant link between students’ parts of speech mastery and their writing achievement. The obtained R-square was .083 indicated that students’ parts of speech mastery was likely to contribute with 8.3% contribution and to affect writing achievement.